Penerapan PSAK Nomor 45 Tentang Pelaporan Keuangan Organisasi Nirlaba Pada Rumah Sakit Bunda Surabaya - Margo Saptowinarko P. (BIP's JURNAL BISNIS PERSPEKTIF, 2012)
The Financial Statements of Not-for- Profit Organizations set in Statement of Financial Accounting Standards (SFAS 45) issued by the Indonesian Institute of Accountants (IAI). This is motivated by the demands of financial transparency and aim for a uniform presentation of financial statements that nonprofit financialstatements can be more easily understood.Financial reporting should provide information about the performance of an organization during a period. Periodic measurement of the changes in the amount and nature of the net resources of a nonbusiness organization and information about the service efforts andaccomplishment of an organizations together represent the information most useful in assessing its performance.In the form of legal entity or business entity, in general, non-profit organization in Indonesia is the Foundation. Bunda Hospital Surabaya is a hospital founded by Bunda foundation with the intent and purpose of doing business in social and humanitarian issues.